The effect of different treatment method on mechanical, physical and characterization of sugarcane bagasse / polypropylene composite / Siti Aisyah Syafiqah Abd Halim - Abd Halim, Siti Aisyah Syafiqah (2020)
This study paper reports on a study of filled composites of polypropylene (PP) and 20 php sugarcane bagasse fiber (SBF). The characterization, physical and mechanical properties have been successfully investigated. The modified SBF filled has been incorporated into PP to compare its properties with untreated SBF filled composite. The compatibility problem between PP matrix and SBF is over comed by modifiying the SBF surface. The surface treatment such as alkali treatment, silane treatment and acid treatment was conducted to modify the SBF. Fourier Transform Infrared (FTIR) spectroscopy was used to study the chemical structure of SBF before and after surface treatments. Composite strength was measured by tensile and impact test. Water absorption test was performed to study the physical properties. As a result, surface treatment can improved the physical and mechanical properties of the composite compared to untreated composite. Hence, the interfacial adhesion between filler and polymer matrix is better after surface modification was done on the filler.